2015
DOI: 10.1007/s11255-015-1142-6
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction and depression among Turkish women with infertile husbands: the invisible part of the iceberg

Abstract: Comparison of these groups indicated similar levels of sexual dysfunction. Nonetheless, we found that women with infertile partners experienced sexual problems related to lubrication and pain, even though they were in the initial stages of the treatment process for infertility. Exposed group had also higher level of depression than the unexposed group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…In a study investigating the effect of male infertility on the sexual function and depression level in Turkish women, 56 women with infertile husbands and 48 women with pregnancy were included (Ozkan, Orhan, Aktas, & Coskuner, ). The mean FSFI score was 19.1 ± 5.5 in the infertile group and 20.0 ± 3.4 in the noninfertile group.…”
Section: Discussionmentioning
confidence: 99%
“…In a study investigating the effect of male infertility on the sexual function and depression level in Turkish women, 56 women with infertile husbands and 48 women with pregnancy were included (Ozkan, Orhan, Aktas, & Coskuner, ). The mean FSFI score was 19.1 ± 5.5 in the infertile group and 20.0 ± 3.4 in the noninfertile group.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Pinborg, Loft, Schmidt, and Andersen (2003) showed, in a study of divorce rates among parents of 3-and 4-year-old twins, that the divorce rate for parents who conceived spontaneously was double that of parents who conceived after assisted reproductive technology (ART) treatment. In contrast, Turkish women with infertile partners had lower levels of marital adjustment than women in couples who spontaneously conceived (Ozkan, Orhan, Aktas, & Coskuner, 2016). Wang et al (2007) compared IVF, ICSI (intracytoplasmic sperm injection), and fertile controls and found that the two infertile groups had less stable marital relationships than the fertile controls.…”
Section: Infertility and Relationship Satisfactionmentioning
confidence: 97%
“…Studies indicate that infertility can have both desirable and undesirable outcomes (Greil, Slauson‐Blevins, & McQuillan, 2010; Verhaak et al, ). For example, among the deleterious effects of infertility on relationships, sex can lose its spontaneity and become more chore‐like rather than a source of pleasure or expression of intimacy within the relationship (Piva, Lo Monte, Graziano, & Marci, ; see also Glover, McLellan, & Weaver, ; Ozkan, Orhan, Aktas, & Coskuner, ). Conversely, infertility can lead to stronger couple relationships (Peterson, Pirritano, Block, & Schmidt, ; Wagner, Wrzus, Neyer, & Lang, ), especially among partners who approach infertility as a shared problem (Greil, ).…”
Section: Education and Awareness Of Reproduction And Infertility Treamentioning
confidence: 99%